PROFILE OF MILLENIAL WOMAN IN POOR HOUSEHOLDS IN SULAWESI UTARA PROVINCE - Anton Tri Wijayanto (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Gender issues among millennials require more focused data-based handling. Especially if this issue is developed within the framework of reducing regional poverty. However, there has been no quantitative analysis that dissects millennial gender data in the poverty framework in more depth. This study aims to obtain more in-depth information about the profile of millennial woman in poor households Using secondary data from the SUSENAS data collection, BPS in 2021 as many as 8,536 respondents spread across all regencies/cities in Sulawesi Utara. Quantitative descriptive analysis was carried out on the millennial generation group variables, gender and poverty variables. The results of the study show that the majority of millennial woman in poor households who are involved in the world of work enter the informal sector. Only a small proportion are included in the formal sector, and even then only as lower-class workers. The government can use the results of this analysis to formulate policies that defend millennial woman in the socio-economic life of society.